Selective protein kinase C inhibition switches time-dependent glucose cardiotoxicity to cardioprotection - Brennan, Sean; Esposito, Simona; Abdelaziz, Muhammad I. M.; Martin, Christopher A.; Makwana, Samir; Sims, Mark W.; Squire, Iain B.; Sharma, Parveen; Chadwick, Amy E.; Rainbow, Richard D. (Frontiers in Cardiovascular Medicine, 2022)
Hyperglycaemia at the time of myocardial infarction has an adverse effect on prognosis irrespective of a prior diagnosis of diabetes, suggesting glucose is the damaging factor. In ex vivo models of ischaemia, we demonstrated that deleterious effects of acutely elevated glucose are PKCα/β-dependent, and providing PKCα/β are inhibited, elevated glucose confers cardioprotection. Challenges with high glucose were trialled as a pre-ischaemic treatment to impart time-limited cardioprotection, with PKCα/β inhibition investigated as a potential enhancement. Freshly isolated non-diabetic rat cardiomyocytes were exposed to elevated glucose to investigate the time-dependence of the protective and toxic effects. High glucose challenge for >7.5 min was cardiotoxic, proarrhythmic and led to contractile failure, whilst cardiomyocytes exposed to metabolic inhibition following 5-min high glucose, displayed time-dependent protection lasting ~15 min. This protection was further enhanced with PKCα/β inhibition. Cardioprotection was measured as a delay in contractile failure and KATP channel activation, improved contractile and Ca2+ transient recovery and increased cell survival. Finally, the effects of pre-ischaemic treatment with high glucose in a whole-heart coronary ligation protocol, where protection was evident with PKCα/β inhibition. Selective PKCα/β inhibition enhances protection suggesting glycaemic control with PKC inhibition as a potential cardioprotective therapeutics in myocardial infarction and elective cardiac surgery.